Comprehensive 3D epigenomic maps define limbal stem/progenitor cell function and identity - Mingsen Li; Huaxing Huang; Bofeng Wang; Shaoshuai Jiang; Huizhen Guo; Liqiong Zhu; Siqi Wu; Jiafeng Liu; Li Wang; Xihong Lan; Wang Zhang; Jin Zhu; et al. (Nature Communications, 2022)
Genome topology provides a structural basis for epigenome-mediated transcriptional regulation in eukaryotes. Here the authors characterized the 3D genome of stratified squamous epithelia. They generated a Hi-C map of human limbal stem/progenitor cells (LSCs) and integrated these data with epigenomics, transcription factor binding maps, and transcriptome data.